PENGARUH BRAND IMAGE DAN PERCEIVED QUALITY TERHADAP WILLINGNESS TO PAY PREMIUM PADA PRODUK UMKM LOKAL - Joko; Tarjono (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
This study aimed to analyze the effect of brand image and perceived quality on willingness to pay premium for local Micro, Small, and Medium Enterprises (MSME) products. Amid increasingly intense market competition with imported goods and national brands, local MSMEs are required to build strong brand image and good perceived quality so that consumers are willing to pay a premium price. A quantitative approach with a causal research design was employed. The study population consisted of consumers who had purchased local MSME products within the past three months in Sukabumi and its surrounding areas. A total of 220 respondents were selected using purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS 24 software. The results show that brand image has a positive and significant effect on willingness to pay premium with a coefficient of 0.45 (p<0.01), and perceived quality has a positive and significant effect with a coefficient of 0.39 (p<0.01). Simultaneously, both variables explain 54.2% of the variance in willingness to pay premium. These findings confirm that strengthening brand image and improving consumer-perceived product quality are key strategies for MSME actors to increase the selling value and competitiveness of local products